A test of the core process account of psychopathology in a heterogenous clinical sample of anxiety and depression: A case of the blind men and the elephant? - Mansell, W.; McEvoy, Peter (Pergamon, 2016)
Many cognitive and behavioral processes, such as selective attention to threat, self-focused attention, safety-seeking behaviors, worry and thought suppression, have their foundations in research on anxiety disorders. Yet, they are now known to be transdiagnostic, i.e. shared across a wide range of psychological disorders. A more pertinent clinical and theoretical question is whether these processes are themselves distinct, or whether they reflect a shared 'core' process that maintains psychopathology. The current study utilized a treatment-seeking clinical adult sample of 313 individuals with a range of anxiety disorders and/or depression who had completed self-report measures of widely ranging processes: affect control, rumination, worry, escape/avoidance, and safety-seeking behaviors. We found that only the first factor extracted from a principal components analysis of the items of these measures was associated with symptoms of anxiety and depression. Our findings supported the 'core process' account that had its origins in the field of anxiety disorders, and we discuss the implications for theory, clinical practice and future research across psychological disorders.